Research and postgraduate studies in higher art education - Narejos Bernabéu, Antonio (Avances en Supervisión Educativa, 2022)
This article delves into the relationship between teaching and research in higher artistic education in Spain, and how the introduction of postgraduate studies in recent years is making it possible for research activities to progressively become a reality in the higher centres in charge of these studies. Firstly, an evolutionary perspective of Spanish regulations in relation to research in the sector is offered. Next, the development at the master’s and doctoral levels in the field of artistic education is reviewed. Finally, an attempt is made to gather the good practices undertaken, both in the autonomous public administrations and in the centres themselves, towards a future normalization of research.